Valorization of Moroccan Pistacia lentiscus L. Leaves: Phytochemical and In Vitro Antioxidant Activity Evaluation Compared to Different Altitudes - Abderrahmane Hadini; Amal Azdimousa; Amine Khoulati; Khalid El bekkaye; Ennoumane Saalaoui (The Scientific World Journal)
This study examined the secondary metabolite content and the antioxidant activities of hydromethanolic P. lentiscus L. leaves extracts at different altitudes. The results indicated that the contents of polyphenols and flavonoids were significantly (p≤0.05) high in the low altitude, unlike the Chl (chlorophyll), tannins, and ascorbic acid, which were reported to have higher content in the high altitude. These results showed that the P. lentiscus L. is more adaptable to higher elevations than low elevation, where the plant was probably stressed. On the other hand, the analyses of correlation between the antioxidant activity and phytochemical content affirmed that the antiradical activity (DPPH) correlated with the content of polyphenols; however, the total antioxidant activity is correlated with the flavonoid content. These results revealed the importance of P. lentiscus L. leaves as a natural antioxidant and gave an idea of the altitude effect on the biochemical parameters of leaves.